Efektivitas Penerapan Pendekatan SAVI Setting Cooperative Script dalam Pembelajaran Matematika Siswa Kelas IX SMP Negeri 33 Makassar - Rizky Ayu Fatimah Ridwan; Alimuddin; Djadir (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This research aimed to determine the effectiveness of implementing SAVI approach with cooperative script setting in students’ mathematics learning of Grade IX SMP Negeri 33 Makassar by clicking refer to the three criteria of effectiveness of learning, i.e students’ learning achievement, students’ activities and responses. The data analysis technique that used was the technique of descriptive and inferential statistical analysis. The results analysis of this research are: 1) the average percentage of students who was taught by SAVI approach with cooperative script setting is greater than 73 (KKM), (2) the average value of normalized gain is 0,79 (high category), (3) the average percentage of students’ activities is 92%, (4) the average percentage of students who gave positive responses to the implementation of learning is 94%, (5) there is a significant difference in mathematics learning achievement before and after the use of the SAVI approach with cooperative script setting. From these results it can be concluded that learning with SAVI approach with cooperative script setting is effective to be used in students’ mathematics learning of Grade IX of SMP Negeri 33 Makassar.